Protein sulfenation as a redox sensor: proteomics studies using a novel biotinylated dimedone analogue. - Charles, R; Schröder, E; May, G; Free, P; Gaffney, P; Wait, R; Begum, S; Heads, R; Eaton, P (2007)
Protein sulfenic acids are reactive intermediates in the catalytic cycles of many enzymes as well as the in formation of other redox states. Sulfenic acid formation is a reversible post-translational modification with potential for protein regulation. Dimedone (5,5-dimethyl-1,3-cyclohexanedione) is commonly used in vitro to study sulfenation of purified proteins, selectively "tagging" them, allowing monitoring by mass spectrometry. However dimedone is of little use in complex protein mixtures because selective monitoring of labeling is not possible. To address this issue, we synthesized a novel biotinylated derivative of dimedone, keeping the dione cassette required for sulfenate reactivity but adding the functionality of a biotin tag. Biotin-amido(5-methyl-5-carboxamidocyclohexane 1,3-dione) tetragol (biotin dimedone) was prepared in six steps, combining 3,5-dimethoxybenzoic acid (Birch reduction, ultimately leading to the dimedone unit with a carboxylate functionality), 1-amino-11-azido-3,6,9-trioxaundecane (a differentially substituted tetragol spacer), and biotin. We loaded biotin dimedone (0.1 mm, 30 min) into rat ventricular myocytes, treated them with H(2)O(2) (0.1-10,000 microm, 5 min), and monitored derivatization on Western blots using streptavidin-horseradish peroxidase. There was a dose-dependent increase in labeling of multiple proteins that was maximal at 0.1 or 1 mm H(2)O(2) and declined sharply below basal with 10 mm treatment. Cell-wide labeling was observed in fixed cells probed with avidin-FITC using a confocal fluorescence microscope. Similar H(2)O(2)-induced labeling was observed in isolated rat hearts. Hearts loaded and subjected to hypoxia showed a striking loss of labeling, which returned when oxygen was resupplied, highlighting the protein sulfenates as oxygen sensors. Cardiac proteins that were sulfenated during oxidative stress were purified with avidin-agarose and identified by separation of tryptic digests by liquid chromatography with on-line analysis by mass spectrometry.